The Impact of Resale on 2-Bidder First-Price Auctions where One Bidder?s Value is Commonly Known - Thomas Tröger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
We consider 2-bidder first-price auctions where one bidder's value is commonly known. Such auctions induce an ineffcient allocation. We show that a resale opportunity, where the auction winner can make a take-it-or-leave-it offer to the loser, increases (reduces) the ineffciency of the market when the buyer with the commonly known value is weak (strong). Resale always reduces all bidders' payoffs and increases the initial seller's revenue.
Keywords: D44; 330; asymmetric first-price auctions; resale; efficiency